Eulobomyia, a new replacement name for Lobomyia Woodley & Arnaud (Diptera: Tachinidae) - Woodley, Norman E.; Arnaud, Jr., Paul H. (Zootaxa, 2008)
A new genus, Lobomyia Woodley & Arnaud (Diptera: Tachinidae), from the Neotropical Region was recently described by us (Woodley & Arnaud, 2008: 32; type species, Lobomyia neotropica Woodley & Arnaud; published 6 June 2008). At the time the manuscript was being prepared, one of us (NEW) checked available nomenclatural resources to ensure the generic name had not been previously used. However, in the interim, the name Lobomyia was published as a new genus of Diptera, Chironomidae from Japan (Niitsuma, 2007: 105; type species, Lobomyia immaculata Niitsuma; published 15 June 2007). We therefore propose a new replacement name here, Eulobomyia, nom. nov. for Lobomyia Woodley & Arnaud. The gender of the name is feminine.